Non-cancer Causes of Death Following Initial Synchronous Bone Metastasis in Cancer Patients - Xu, Yao; Abdelazeem, Basel; Abbas, Kirellos Said; Lin, Yile; Wu, Haixiao; Zhou, Fei; Peltzer, Karl; Chekhonin, Vladimir P.; Li, Shu; Li, Huiyang; Ma, Wenjuan; Zhang, Chao (Frontiers in Medicine, 2022)
Abstract Purpose To investigate non-cancer causes of death in cancer patients with synchronous bone metastasis based on the Surveillance, Epidemiology, and End Results (SEER) database. Methods The retrospective cohort study included malignant cancer patients with synchronous bone metastasis diagnosed from 2010 to 2018 in SEER database.The frequencies and proportion of non-cancer causes of death were calculated and analyzed in different gender, age and race subgroups. Results A total of 97,997 patients were deceased and included into the current study and 6,782 patients were died of non-cancer causes with a male predominance (N=4,515, 66.6%). Around half of deaths (N= 3,254, 48.0%) occurred within 6 months after diagnosis while 721 patients were deceased after 3 years. Lung and bronchus cancer, prostate cancer, breast cancer, kidney and renal pelvis cancer and liver cancer were proved to be the top five cancer types resulting in non-cancer caused death. Cardiovascular and cerebrovascular disease was the leading non-cancer cause of death (N=2,618), followed by COPD and associated conditions (N=553) and septicemia, infectious and parasitic diseases (N=544). Sub-analyses stratified by gender, age and race were performed and the similar results with slightly difference were observed. Conclusions Cardiovascular and cerebrovascular disease was the main non-cancer cause of death in cancer patients with synchronous bone metastasis. Other non-cancer causes included COPD, septicemia, infectious and parasitic diseases and so on. These findings should be considered by physicians. Physicians can counsel cancer patients with bone metastasis regarding survivorship with death causes screening and focus on prevention of non-cancer deaths.